The ever-changing business of e-commerce-net benefits while designing a new platform for small companies - Costa, P.; Rodrigues, H. (Review of Managerial Science, 2024)
Electronic commerce has allowed businesses to grow globally by breaking down barriers that many believed could not be overcome. Although large companies often outperform small and medium-sized businesses, e-commerce allows them to compete with them in some areas. Surprisingly, there is a lack of theoretical evidence regarding e-commerce net benefits for a small and medium-sized business that operates in the context of Business-to-Business. We expand the previous model of information system success by analyzing the role of game dynamics and user satisfaction in the intention to use e-commerce and its net benefits in the success of the new e-commerce platform. To help predict the success of a new e-commerce platform we collect 522 responses from a pool of clients of a small company that sells products to Hotels, Restaurants, and Cafes. Ease of use is the main variable that affects customer satisfaction and their intention to use e-commerce The company will only achieve e-commerce net benefits if these conditions are met. The results contribute to a better understanding of e-commerce net benefits while developing a new e-commerce platform and provide valuable practical contributions for small companies that have limited marketing and information systems.